Consumer engagement with football brands on Facebook - Almeida, Nuno Filipe Castro (2021)
The growth of social media has forced brands to adapt the scope of their activities in terms of brand management, consumer engagement and customer communications. Football brands have recently started to understand the relevance of social media as a tool for exploiting the enormous potential they possess, much due to their well-established brand awareness, brand identity and, most of all, the passion they more easily trigger in fans. The goal of this research is to determine the most influential motivations that trigger consumers to engage with a football brand on Facebook. Furthermore, we want to understand if between brand love, brand image and consumer engagement influence brand loyalty towards football brands. To do so, we have collected data from 214 respondents that were questioned about this subject, after which we performed correlation analysis in order to test these relations. Our findings point out that entertainment, personal identity and social influence are the most influential types of motivations to engage with a football brand on Facebook. Trust in the brand, despite not showing the same relevance, also came out as a significant variable. Other results indicate that there is a positive relation between brand love, brand image, consumer engagement and, lastly, brand loyalty. Our findings and the respective managerial implications they might present are discussed, also providing indications and suggestions regarding future researches concerning this subject.